Prognostic factors in metastatic nasopharyngeal carcinoma - Toumi,Nabil (2022)
Abstract Introduction: Nasopharyngeal carcinoma has the highest metastatic potential of all head and neck cancers. The survival time of patients with nasopharyngeal carcinoma has improved significantly in the last decades due to the use of combination of chemotherapy and radiotherapy, as well as advances in radiotherapy techniques. However, appropriately 30% of patients with nasopharyngeal carcinoma suffer a poor prognosis, mainly due to distant metastasis. Objective: The study aimed to identify the survival and prognostic factors in metastatic nasopharyngeal carcinoma. Methods: A retrospective analysis was conducted in patients treated for synchronous metastatic nasopharyngeal carcinoma or metachronous metastatic nasopharyngeal carcinoma for 14years (2003–2016). Overall survival was analyzed using the Kaplan-Meier method and compared using the log-rank test for the whole population and both groups of patients. Multivariate analysis was performed using the Cox model; p-values < 0.05 were considered to indicate statistical significance. Results: One hundred and twelve patients with metastatic nasopharyngeal carcinoma were included (51 patients with metastatic nasopharyngeal carcinoma, and 61 patients with metachronous metastatic nasopharyngeal carcinoma). In the whole population, the median overall survival was 10 months (1–156 months). In the multivariate analysis, female gender, poor performance status (WHO > 1) and metachronous metastasis were independent prognostic factors. In the metastatic nasopharyngeal carcinoma patients, the median overall survival was 13 months (1–156 months). In multivariate analysis, independent prognostic factors were non-oligometastatic disease, severe (G3–G4) chemotherapy toxicity and the lack of nasopharyngeal and metastatic site irradiation. In the metachronous metastatic nasopharyngeal carcinoma patients, the median overall survival was 7 months (1–41 months). In multivariate analysis, the poor performance status (WHO > 1) was an independent metastatic nasopharyngeal carcinoma prognostic factor. Conclusion: Oligometastatic patients with synchronous metastatic nasopharyngeal carcinoma had better survival. The locoregional treatment of primitive nasopharyngeal carcinoma improved survival in patients with metastatic nasopharyngeal carcinoma who responded to induction chemotherapy. Local irradiation of metastatic sites improved survival of metastatic nasopharyngeal carcinoma patients. Grade 3 or 4 chemotherapy toxicity altered survival among patients with synchronous metastatic nasopharyngeal carcinoma.